ABREVIASI BAHASA GAUL REMAJA - Kiki Zakiah Nur (Kelasa, 2018)
AbstrackThis paper analyzes slang language abreviations. This research method is descriptive, which is to make systematic, factual and accurate statements about the facts and nature of the data. The aim is to find and describe the forms of abreviation found in teen slang. The results of the analysis showed that there were abreviations in the form of abbreviations, acronyms, a combination of abbreviations and acronyms, and beheading. In abreviations in the form of abbreviations, found an abbreviation of Indonesian, an abbreviation of English, and a combination of Indonesian and English abbreviations. In the form of acronyms, found acronyms from the Indonesian language and acronyms from the English language. The Indonesian acronym consists of two syllables, three syllables, four syllables, five syllables, and two words. The acronym for English consists of one syllable (a combination of the initial letters of the word) and two syllables. In the form of decapitation, the final part of the word that is decapitated or eliminated is found.AbstrakMakalah ini menganalisis abreviasi bahasa gaul. Metode penelitian ini adalah deskriptif, yakni membuat pencandraan secara sistematis, faktual, dan akurat mengenai fakta-fakta dan sifat data. Tujuannya adalah menemukan dan mendeskripsikan bentuk-bentuk abreviasi yang terdapat pada bahasa gaul remaja. Hasil analisis menunjukkan bahwa ditemukan abreviasi berupa singkatan, akronim, gabungan singkatan dan akronim, serta pemenggalan. Pada abreviasi berupa singkatan, ditemukan singkatan dari bahasa Indonesia, singkatan dari bahasa Inggris, dan gabungan singkatan bahasa Indonesia dan bahasa Inggris. Pada abreviasi berupa akronim, ditemukan akronim dari bahasa Indonesia dan akronim dari bahasa Inggris. Akronim dari bahasa Indonesia terdiri dari dua suku kata, tiga suku kata, empat suku kata, lima suku kata, dan dua kata. Akronim dari bahasa Inggris terdiri dari satu suku kata (gabungan huruf awal kata) dan dua suku kata. Pada abreviasi berupa pemenggalan ditemukan bagian akhir kata yang dipenggal atau dihilangkan.